2008
DOI: 10.1038/sc.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

A structured review of outcome measures used for the assessment of rehabilitation interventions for spinal cord injury

Abstract: Objectives: To review the measurement properties of outcome measures of function or mobility currently used in the context of spinal cord injury (SCI). Methods: A keyword search of multiple databases to identify original papers. Papers were reviewed where they had included an evaluation, of people with SCI, of the psychometric properties of an outcome measure, which included functional or mobility domains. Information was extracted concerning item generation, ease and intended method of use and scale propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…2 However, the assessment of reliability at that stage required consensus on the number and types of aids and assistants with which the person was walking; further, there are claims that further evidence of reliability and responsiveness is needed. 15,[20][21][22] Nevertheless, reliability studies on the WISCI are available only in chronic SCI patients. 8,9 Recently, Marino et al 8 reported that for chronic SCI patients, the IRR and intrarater reliability was 1.00 for SS WISCI II.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the assessment of reliability at that stage required consensus on the number and types of aids and assistants with which the person was walking; further, there are claims that further evidence of reliability and responsiveness is needed. 15,[20][21][22] Nevertheless, reliability studies on the WISCI are available only in chronic SCI patients. 8,9 Recently, Marino et al 8 reported that for chronic SCI patients, the IRR and intrarater reliability was 1.00 for SS WISCI II.…”
Section: Discussionmentioning
confidence: 99%
“…The FIM shows good evidence of reliability and validity and is routinely used in spinal rehabilitation. 12 The depression, anxiety and stress scales (DASS-21) 13 were administered on an individual's admission to the Unit. This 21-item questionnaire, derived from the original 42-item DASS, consists of three subscales designed to measure the emotional states of depression, anxiety and stress.…”
Section: Participantsmentioning
confidence: 99%
“…Research has demonstrated the NAC to be a psychometrically reliable and valid assessment tool 24,25 and a recent review found it to be one of the best measures of outcomes in SCI rehabilitation. 26 This study will observe and compare rehabilitation outcomes, in the ten aforementioned domains of the NAC, between patients with T-SCI and NT-SCI undergoing the same rehabilitation programme at a SIC. This study aims to draw conclusions regarding whether NT-SCI patients benefit from the same rehabilitation programme as T-SCI patients and, therefore, whether it is advisable for them to be admitted and treated similarly.…”
Section: Introductionmentioning
confidence: 99%